Risk management in banking - Bessis, Joel. (Chichester, West Sussex, UK : Wiley, 2015)
"The seminal guide to risk management, streamlined and updated Risk Management in Banking is a comprehensive reference for the risk manage ment industry, covering all aspects of the field. Now in its fourth edi tion, this useful guide has been updated with the latest information on ALM, Basel 3, derivatives, liquidity analysis, market risk, structured products, credit risk, securitizations, and more. The new companion we bsite features slides, worked examples, a solutions manual, and the new streamlined, modular approach allows readers to easily find the inform ation they need. Coverage includes asset liability management, risk-bas ed capital, value at risk, loan portfolio management, capital allocatio n, and other vital topics, concluding with an examination of the financ ial crisis through the utilisation of new views such as behavioural fin ance and nonlinearity of risk. Considered a seminal industry reference since the first edition's release, Risk Management in Banking has been streamlined for easy navigation and updated to reflect the changes in t he field, while remaining comprehensive and detailed in approach and co verage. Students and professionals alike will appreciate the extended s cope and expert guidance as they: Find all "need-to-know" risk manag ement topics in a single text Discover the latest research and the ne w practices Understand all aspects of risk management and banking man agement See the recent crises - and the lessons learned - from a new perspective Risk management is becoming increasingly vital to the ba nking industry even as it grows more complex. New developments and adva ncing technology continue to push the field forward, and professionals need to stay up-to-date with in-depth information on the latest practic es. Risk Management in Banking provides a comprehensive reference to th e most current state of the industry, with complete information and exp ert guidance"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by p ublisher.
Keywords: Bank management; Risk management; Asset-liability management